Identifikasi Pengunjung Pada Pantai Panrita Lopi, Kecamatan Muara Badak - Noor, Muhammad Fauzan; Iswandari, Rini Koen; Zulfiani, Dini (Samarinda State Polytechnic, 2021)
Panrita Lopi Beach is one of the natural tourist destinations that needs to be surveyed by visitors in order to identify and determine strategies for developing tourist attractions and also marketing in Kutai Kartanegara Regency. This study aims to analyze the characteristics of tourists and travel patterns of tourists who visit and to determine the perception of the level of tourist satisfaction with infrastructure products, public facilities and tourism facilities in this tourist destination. The main variables used in segmenting comprise: Geographic Segmentation, Demographic Segmentation, Psychographic Segmentation, and Behavior-based Segmentation. This research is a type of survey research with a qualitative descriptive approach. I carried out data collection from primary data sources and secondary data sources. The sample used in this study is a non-probability sampling technique by accidental sampling, namely a sampling technique based on chance, anyone who coincidentally meets a researcher can be used as a sample, if it is deemed that the person who was met is suitable as a data source. Data that has been collected from research results related to typology (characteristics, travel patterns) and visitor perceptions can be analyzed descriptively qualitatively. The analyzed data comes from surveys through questionnaires that have been given to visitors, including data on visitor profiles, visitor travel patterns, and visitor perceptions about this Panrita Lopi beach.